MODEL ANALISIS KEBIJAKAN PUBLIK DALAM PROGRAM BEASISWA SANTRI BERPRESTASI KEMENAG - Muhammad Chabibi (Zawiyah: Jurnal Pemikiran Islam, 2019)
Islamic boarding schools (Pesantren) as genuine Islamic education institutions from Indonesia have a very important role in improving the quality of human resources in accordance with Indonesian national goals to educate the Indonesian people. The Ministry of Religious Affairs of the Republic of Indonesia has a policy focused on empowering and improving the quality of students of Islamic Boardings (Santri), especially in the academic field. The policy is the awarding of scholarships to outstanding students or commonly referred to as the Achievement Santri Scholarship Program (PBSB) to be able to continue their studies at favourite universities in Indonesia. However, the implementation of the policy certainly faces obstacles so that it needs an evaluation study for the achievement of the program according to its objectives. This article tries to analyze the existing policy analysis model in the Achieving Santri Scholarship Program with a six-stage model developed by Newton and Van Deth. The findings are that the program could not be separated from the outcome problems and feedback from the policy so that there are scholarship recipients who have not been able to maximize the service to the pesantren both in terms of administration and social environment.